Ethylhexadecyldimethylammonium bromide, a quaternary ammonium compound, controls inflammatory response through NRF2 pathway in a human immortalized keratinocyte cell line - Aubry, Lise; Vallion, Romain; Salman, Sara; Damiens, Marie-Hélène; Ferret, Pierre-Jacques; Kerdine-Römer, Saadia (Frontiers in Toxicology, 2023)
Many everyday products contain quaternary ammonium compounds (QAC) and some of them are known to be skin irritants such as benzalkonium chloride. Others, such as didecyldimethylammonium chloride, have been shown to cause allergic contact dermatitis. Ethylhexadecyldimethylammonium bromide (EHD) is a QAC for which sensitization potential is not clearly known. Therefore, we have studied its mechanism in human keratinocytes (KC), the main cells of the epidermis. We used the well described human KC cell line KERTr exposed to EHD, cinnamaldehyde (CinA), a well-known skin sensitizer, and a mixture of both. Since chemical sensitizers are known to activate the transcription factor nuclear factor (erythroid-derived 2)-like 2 (NRF2), leading to cellular detoxification and suppressed proinflammatory cytokines, protein, or mRNA expression of NRF2 pathway-related enzymes and pro-inflammatory cytokines were investigated by western-blot and RT-qPCR. The activity of the NRF2 pathway on inflammation was studied by RT-qPCR in NRF2-invalidated KERTr cells. We showed that EHD cannot induce the NRF2 pathway, unlike contact sensitizers like CinA. EHD triggers an inflammatory response by inducing the mRNA expression of pro-inflammatory cytokines such as IL-1β or IL-6. Moreover, mixing EHD and CinA inhibits the effect of CinA on the NRF2 pathway and mitigates the inflammatory response induced by EHD alone. EHD treatment of KERTr cells in which NRF2 has been invalidated showed an exacerbation of the inflammatory response at the transcriptional level. Hence, EHD may elicit an inflammatory response in KC via the NF-kB pathway, which could lead to irritation when applied to the skin. This inflammation is negatively controlled by the basal activity of the NRF2 pathway